Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1968
DOI: 10.1007/bf02668964
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic fatty acids: Separation from straight‐chain fatty acids by urea adducting

Abstract: A mixture containing 37% cyclic and 63% straight‐chain fatty acids, made by high‐temperature treatment of linseed oil fatty acids with alkali, was separated by the urea adduct method to give unsaturated cyclic fatty acids (nonadduct) in 95% purity and 90–95% yeild. Previous reports from this Laboratory describe a process for separating cyclic fatty acids from stearic acid by hydrogenation followed by crystallization at −40C. The urea adduct method avoids hydrogenation and low‐temperature crystallization, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Schofield and Cowan demonstrated that linolenic acid could be converted to a cyclized structure by heating in the presence of solvent and alkali (1). Subsequent papers have concerned themselves with methods for improving the preparation and yields of saturated cyclized product (2), its separation from straight chain fatty acids (3), determination by gas liquid chromatography (GLC) (4), and a structural study of these products as mixtures of the corresponding saturated and aromatic isomers (5). Extensive earlier structural work has been reviewed by Friedrich (5), including work on cyclic products from eleostearate.…”
Section: Introductionmentioning
confidence: 99%
“…Schofield and Cowan demonstrated that linolenic acid could be converted to a cyclized structure by heating in the presence of solvent and alkali (1). Subsequent papers have concerned themselves with methods for improving the preparation and yields of saturated cyclized product (2), its separation from straight chain fatty acids (3), determination by gas liquid chromatography (GLC) (4), and a structural study of these products as mixtures of the corresponding saturated and aromatic isomers (5). Extensive earlier structural work has been reviewed by Friedrich (5), including work on cyclic products from eleostearate.…”
Section: Introductionmentioning
confidence: 99%
“…Pure cyclopropenoic fatty acids, such as malvalic and sterculic acids, which are of interest for lipid analysis as well as biochemical studies and chemical reactions, are not commercially available. Fractionation by urea adduct formation is known to yield concentrates of cyclopropenoic fatty acids together with unsaturated fatty acids (15). Separation of cyclopropenoic fatty acids by spinning band distillation requires relatively large proportions of starting material (16).…”
Section: Resultsmentioning
confidence: 99%